Fueling Diversity in the Subsurface: Composition and Age of Dissolved Organic Matter in the Critical Zone - Benk, Simon A.; Yan, Lijuan; Lehmann, Robert; Roth, Vanessa-Nina; Schwab, Valérie F.; Totsche, Kai Uwe; Küsel, Kirsten; Gleixner, Gerd (Frontiers in Earth Science, 2019)
Surface ecosystems are rapidly changing on a global scale and it is important to understand how this influences aquifers in the subsurface, as groundwater quality is a major concern for future generations. Dissolved organic matter (DOM) contains molecular and isotopic signals from surface-derived inputs and from the biotic and abiotic subsurface environment and is therefore ideal to study the connectivity between both environments. Therefore, we evaluated a 3-year time series of DOM composition using ultrahigh resolution mass spectrometry and age using 14C accelerator mass spectrometry along a hillslope well transect in the fractured bedrock of the Hainich Critical Zone Exploratory, Germany. We found a wide range of DOM 14C depletion, from Δ14C = -47.9 to Δ14C = 782.4, within different zones of the shallow groundwater. The 14C content of DOM mirrored the connectivity of the aquifers to the surface. The composition of DOM was highly interrelated with its 14C age. The proportions of surface-derived DOM components decreased with DOM age, whereas microorganism-derived DOM components increased. The intensity of surface-sourced DOM signals differed between the wells and likely reflected the hydrological complexity of fractured-rock environments. During recharge, DOM was more enriched in Δ14C, contained more surface-derived molecular components and was more diverse. As a potential response to the varying DOM substrate, bacterial 16S rRNA gene analysis revealed community evolution and increased bacterial diversity during recharge. The influx of diverse, surface-derived DOM potentially fueled evolution within the autochthonous bacterial communities, as in contrast to DOM, the bacterial community did not retreat to the initial diversity and community composition during the recession period. Our results demonstrate on the one hand that combined analyses of the composition and age of groundwater DOM strongly contribute to the understanding of interconnections, community evolution and the functioning of subsurface ecosystems and on the other hand that changes in surface ecosystems have an imprint on subsurface ecosystems.